2017
DOI: 10.1093/hmg/ddx140
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell modelling of HLHS underlines the contribution of dysfunctional NOTCH signalling to impaired cardiogenesis

Abstract: Hypoplastic left heart syndrome (HLHS) is among the most severe forms of congenital heart disease. Although the consensus view is that reduced flow through the left heart during development is a key factor in the development of the condition, the molecular mechanisms leading to hypoplasia of left heart structures are unknown. We have generated induced pluripotent stem cells (iPSC) from five HLHS patients and two unaffected controls, differentiated these to cardiomyocytes and identified reproducible in vitro ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 56 publications
3
58
0
Order By: Relevance
“…Five out of seven variants tested were de novo, adding to the evidence for pathogenicity; the remaining variants were transmitted from unaffected parents indicating incomplete penetrance. Previous sequencing studies of CHD have identified an association of NOTCH1 variants in cardiac malformations including bicuspid aortic valve, aortic valve stenosis, coarctation of the aorta and hypoplastic left heart syndrome and TOF (43)(44)(45)(46)(47). However, the extent of NOTCH1 variant contribution to TOF has not been recognised until now.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of seven variants tested were de novo, adding to the evidence for pathogenicity; the remaining variants were transmitted from unaffected parents indicating incomplete penetrance. Previous sequencing studies of CHD have identified an association of NOTCH1 variants in cardiac malformations including bicuspid aortic valve, aortic valve stenosis, coarctation of the aorta and hypoplastic left heart syndrome and TOF (43)(44)(45)(46)(47). However, the extent of NOTCH1 variant contribution to TOF has not been recognised until now.…”
Section: Discussionmentioning
confidence: 99%
“…One hESC line (H9, WiCell) one neonatal iPSC line (Neo1, male [38,39]) and one adult iPSC line (AD3, from a 37-year-old female [40]) were adapted from MEF-supported to feeder-free culture conditions on 6 well plates coated with growth factor-reduced Matrigel basement membrane matrix (GFRM; Corning, New York) in TeSR1 (Stem Cell Technologies, Vancouver, Canada) defined medium. Cells were fed daily and passaged every 5 days at a ratio of up to 1:10 using 0.02% versene EDTA (Lonza, Basel, Switzerland).…”
Section: Materials and Methods Hesc Culture And Differentiationmentioning
confidence: 99%
“…Previous sequencing studies of CHD have identified an association of NOTCH1 variants in left-sided cardiac malformations including bicuspid aortic valve, aortic valve stenosis, coarctation of the aorta and hypoplastic left heart syndrome (27)(28)(29)(30). Like TOF, the causative NOTCH1 variants described for these conditions are mostly missense with a small number of LOF variants located throughout the NOTCH1 protein.…”
Section: Discussionmentioning
confidence: 99%